2014
DOI: 10.1089/fpd.2014.1738
|View full text |Cite
|
Sign up to set email alerts
|

Vidas UP–Enzyme-Linked Fluorescent Immunoassay Based on Recombinant Phage Protein and FluorescenceIn SituHybridization as Alternative Methods for Detection ofSalmonella entericaSerovars in Meat

Abstract: Several methods for the rapid and specific detection of Salmonella spp. in meat have been described. This study was conducted to evaluate the capability of the VIDAS(®) UP (SPT [Salmonella Phage Technology]), an enzyme-linked fluorescent immunoassay method, and fluorescence in situ hybridization (FISH) to complement the International Organization for Standardization Method 6579 (ISO) in detecting Salmonella spp. from beef, pork, and poultry meat samples. The meat was inoculated with a mixture of Salmonella spp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The results showed that FISH probes represents an effective tool for detecting and enumerating pathogens in wastewater due to its efficiency, specifity and sensivity, even when viable but non-culturable (VBNC) cells are present. FISH method has been previously used with good results for identification of Salmonella in clinical samples (Nordentoft et al, 1997;O'Keefe et al, 2001;Frickman et al, 2013) or in artificially inoculated environmental samples (Zadernowska et al, 2014;Sha et al, 2013). Almeida et al (2010; reported the use of a PNA FISH probe to detect Salmonella in natural fountain water and biofilms.…”
Section: Salmonellamentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that FISH probes represents an effective tool for detecting and enumerating pathogens in wastewater due to its efficiency, specifity and sensivity, even when viable but non-culturable (VBNC) cells are present. FISH method has been previously used with good results for identification of Salmonella in clinical samples (Nordentoft et al, 1997;O'Keefe et al, 2001;Frickman et al, 2013) or in artificially inoculated environmental samples (Zadernowska et al, 2014;Sha et al, 2013). Almeida et al (2010; reported the use of a PNA FISH probe to detect Salmonella in natural fountain water and biofilms.…”
Section: Salmonellamentioning
confidence: 99%
“…The FISH assay is less sensitive to inhibitory substances than PCR and has shown to be a very useful tool for phylogenetic, ecological, diagnostic and environmental microbiology studies (Bottari et al, 2006). It has been successfully used for detection and identification of different pathogens, including Salmonella, in foods, surface water, drinking water and wastewater (Zadernowska et al, 2014;Sha et al, 2013;Almeida et al, 2011;Almeida et al, 2010;Gironés et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous alternative methodologies exist for the rapid analysis of foodborne pathogens, including immunoassays (e.g. automated Vidas [4,5] and lateral flow immunochromatography [6][7][8]), and quantitative PCR (qPCR) (e.g.…”
Section: Introductionmentioning
confidence: 99%